جودة التشطيب وأثره على التصميم الداخلي للمباني جمالياً ووظيفياً (Comprehensive Journal of Science, 2025)
The quality of finishing is considered one of the fundamental factors that affect the aesthetic aspect of interior design in buildings. High-quality finishing can enhance the aesthetic and functional aspects of a space, while poor finishing may lead to a reduction in both the value and beauty of the building. The quality of finishes and the use of good raw materials are highly important for buildings, as they represent the visible and perceived surfaces in both interior and exterior parts of the structure.This article discusses the importance of finishing quality in the interior design of buildings and its direct impact on the overall aesthetics of spaces. The study highlights several aspects related to the quality of materials used, precision in execution, and the extent to which colors and forms align with the concept of interior design.